2018
DOI: 10.9734/mrji/2018/40552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of the Arr-2 Gene in Escherichia coli and Klebsiella pneumoniae Resistant to Rifampicin in Abidjan, Côte D'Ivoire

Abstract: Aims: The aim of this study was to demonstrate the presence of rifampicin resistance arr-2 gene in certain enterobacteria of clinical origin from various biological products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…E. coli is the one which presents the greatest prevalence of resistance (56.7%) even if the 44% presented by K. pneumoniae are not negligible. The high prevalence of ESBLs in this study, as well as some reported in Côte d' d'Ivoire (Guessennd et al, 2011;Gadou et al. 2018) and in other parts of Africa (Togo et al, 2014;Saravanan et al, 2018;Ouchar et al, 2019), show that the spread of ESBL-producing Enterobacteriaceae in an African context remains a very worrisome phenomenon.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…E. coli is the one which presents the greatest prevalence of resistance (56.7%) even if the 44% presented by K. pneumoniae are not negligible. The high prevalence of ESBLs in this study, as well as some reported in Côte d' d'Ivoire (Guessennd et al, 2011;Gadou et al. 2018) and in other parts of Africa (Togo et al, 2014;Saravanan et al, 2018;Ouchar et al, 2019), show that the spread of ESBL-producing Enterobacteriaceae in an African context remains a very worrisome phenomenon.…”
Section: Discussionsupporting
confidence: 74%
“…blaTEM, blaSHV and blaCTX-M are the main variants of genes coding for resistance in Enterobacteriaceae with the latest one (Ahmad and Khadija, 2019). In Côte d'Ivoire, recent studies have reported the spread of ESBL-producing strains of E. coli and K. pneumoniae in various infections (Tahou et al, 2017;Gadou et al, 2018) although the setup since 2002 of an observatory of antimicrobial resistance is dedicated to actions contributing to fight against the spread of resistant or multi-resistant bacteria (Ouédraogo et al, 2017). In addition, information on genetic variants and intragenic mutations encoding these resistances are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The only rifampicin resistance mechanism harboured by our strains was the one linked to ADP-ribosyltransferase (arr) genes 2 and 3, revealed exclusively in the wastewater samples. The arr-1, arr-2 and arr-3 genes carried by class I integrons have been described in Gram-negative bacilli strains in Europe and Asia [64]. The arr-2 gene which was the most frequently detected in the selected strains, particularly in influent samples, has been reported to be associated with several transposons and integrons in K. pneumoniae strains [65].…”
Section: Discussionmentioning
confidence: 99%